PLA nano- and microparticles for drug delivery: An overview of the methods of preparation - Lassalle, Verónica Leticia (2007)
The controlled release of medicaments remains the most convenient way of drug delivery. Therefore, a wide variety of reports can be found in the open literature dealing with drug delivery systems. In particular, the use of nano- and microparticles devices has received special attention during the past two decades. PLA and its copolymers with GA and/or PEG appear as the preferred substrates to fabricate these devices. The methods of fabrication of these particles will be reviewed in this article, describing in detail the experimental variables associated with each one with regard to the influence of them on the performance of the particles as drug carriers. An analysis of the relationship between the method of preparation and the kind of drug to encapsulate is also included. Furthermore, certain issues involved in the addition of other monomeric substrates than lactic acid to the particles formulation as well as novel devices, other than nano- and microparticles, will be discussed in the present work considering the published literature available. © 2007 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.